2016
DOI: 10.15761/icst.1000189
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages directed approaches are paramount for effective cancer immunotherapies

Abstract: Macrophages are double edge sword component of immunity and display phenotypical and functional plasticity which enable them to both promote and eliminate established tumors. Under the influence of immunosuppressive tumor microenvironment, tumor infiltrating iNOS+ and CD11b+ M-1 regulatory macrophages get polarized to Tumor associated macrophages (TAM) which are Ym-1 and Arginase+ iNOS-(M-2) and tropic to variety of tumors. Increased density of TAM in the variety of tumors has been correlated with poor prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Among proteins that were uniquely up-regulated in M1 macrophages, seven proteins including IFIT1, IFIT2, IFIT3, CD14, CD38, CD40, and CXCL10 had been reported as M1 biomarkers or cytokines/chemokines in previous studies (33)(34)(35). Similarly, the uniquely up-regulated protein in M2 macrophage, TGM2, had also been used as a M2 biomarker (30).…”
Section: Differentially Expressed Proteins Among Three Subtypes Of Human Thp-1 Macrophagesmentioning
confidence: 99%
“…Among proteins that were uniquely up-regulated in M1 macrophages, seven proteins including IFIT1, IFIT2, IFIT3, CD14, CD38, CD40, and CXCL10 had been reported as M1 biomarkers or cytokines/chemokines in previous studies (33)(34)(35). Similarly, the uniquely up-regulated protein in M2 macrophage, TGM2, had also been used as a M2 biomarker (30).…”
Section: Differentially Expressed Proteins Among Three Subtypes Of Human Thp-1 Macrophagesmentioning
confidence: 99%
“…Due to this characteristic, these cells are now known as double-edge component of immunity as well. Many studies have demonstrated that these cells can enhance the progression as well as control many infectious and tumor [1] diseases. Both peripheral and tissue macrophages together constitute the reticuloendothelium system which plays a major role in both sensing microbial antigens and their subsequent eradication [2].…”
Section: Introductionmentioning
confidence: 99%